Late Ottoman society : the intellectual legacy - Özdalga, Elisabeth, 1946- (London ; New York : RoutledgeCurzon, 2005)
"This volume brings together a set of essays dealing with intellectual developments in late Ottoman society. Under the impact of European expansionism and modernization the Ottoman Empire underwent profound transformations. Important features were the development of a market economy and modern political and administrative structures; the splitting up of the empire into separate nation-states; and the coming into being of a professional middle class and various groups of modern intellectuals."--Jacket
1. Ottoman sources of Kemalist thought / Erik-Jan Zürcher -- 2. Blueprints for a future society : late Ottoman materialists on science, religion, and art / Şükrü Hanioğglu -- 3. Whom did Ahmed Cevdet represent? / Christoph K. Neumann -- 4. Women in late Ottoman intellectual history / Elizabeth B. Frierson -- 5. Turban and fez : ulema as opposition / İsmail Kara -- 6. Pan-Islamism in practice : the rhetoric of Muslim unity and its uses / Adeeb Khalid -- 7. 'Kütüp ve Resail-i Mevkute' : printing and publishing in a multi-ethnic society / Johann Strauss -- 8. Christian community schools during the Ottoman reform period / Akşin Somel -- 9. Levantine state muftis : an Ottoman legacy? / Jakob Skovgaard-Petersen -- 10. Albanian students of Mekteb-i Mülkiye : social networks and trends of thought / Nathalie Clayer.
Simultaneously published in the USA and Canada.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Turkey -- Social conditions -- 1288-1918.; Turkey -- Economic conditions -- 1288-1918.; Scholars -- Turkey; Turkey -- Intellectual life -- 19th century; Turkey -- Civilization; Turkey -- History -- Ottoman Empire, 1288-1918.; Syria -- History -- 1516-1918.; Albania -- History -- 1878-1912.; Turkey -- Civilization -- 1288-1918.; Savants -- Empire ottoman; Empire ottoman -- Conditions sociales; Empire ottoman -- Conditions économiques.; Empire ottoman -- Vie intellectuelle -- 19e siècle.; Empire ottoman -- Civilisation; Empire ottoman -- Histoire; Syrie -- Histoire -- 1516-1918.; Albanie -- Histoire -- 1878-1912.; Asie Mineure -- Vie intellectuelle -- 19e siècle.; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Civilization; Economic history; Intellectual life; Scholars; Social conditions; Albania; Syria; Turkey; Intellektueller; Sozialer Wandel; Osmanisches Reich; Geestesgeschiedenis; 1288-1918; Electronic books; History